The dominant factors affecting agricultural land use (rice field) change in Yogyakarta Special Province - Hadi Sabari Yunus; Rika Harini (Indonesian Journal of Geography, 2005)
The research was conducted in Yogyakarta Special Province. The main objective of this research is to find out the main factors influencing the change in agricultural land use especially rice field. The data used in this research is time series from 1980 to 2000. They were obtainedfrom several institutions such as: Central Bureau of Statistics (BPS), National Agency of Land Affairs (BPN) and Department ofAgriculture (Dinas Pertanian). Descriptive analysis and statistical test were performed against those data to find out the influence of geographic factors i.e. the population growth, the road development and the extension of built up area on the change in agricultural land use especially rice field. Distributed lag model is used to analyze the effect of road's length on agricultural land use change. The level and magnitude of relationship between areas of agricultural land use change and built up area, number of people and road length are calculated using linear regression.The research shows that the period of 1980 - 2000 in Yogyakarta Special Province has indicated very significantly the increase in population, the development of road and the extension of built up area. For the time being, agricultural land mainly in Sleman Regency, Bantul Regency and Yogyakarta Municipality has decreased. Sleman regency performed the largest decrease of rice field and followed after then by Bantul regency and Yogyakarta Municipality. The regency of Kulon Progo and Gunung Kidul have experienced reverse phenomenon i.e. the increase of rice field during this period. Individually or simultaneously, three variables used in this research (number of people, road's length and built up area) have significantly influenced the agricultural land use.